2020
DOI: 10.1186/s41182-020-00288-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 knowledge, beliefs, prevention behaviours and misinformation in the context of an adapted seasonal malaria chemoprevention campaign in six northern Nigerian States

Abstract: Background Seasonal malaria chemoprevention (SMC) using sulfadoxine-pyrimethamine and amodiaquine is an efficacious intervention for protection of children against Plasmodium falciparum malaria during the rainy season. In response to the global COVID-19 pandemic, Malaria Consortium adapted its SMC delivery model to ensure safety of distributors, data collectors and beneficiaries. We conducted a SMC monitoring survey in July 2020 in the states of Bauchi, Jigawa, Kano, Katsina, Sokoto and Yobe, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Education and training on health/eHealth literacy were required for the public communities or individuals to increase their ability to differentiate reliable information from the rumors. ( Durodolu and Ibenne, 2020 ; Wormer, 2020 ; Mokhtari and Mirzaei, 2020 ; Mondiale de la Santé, 2020 ; Gottlieb and Dyer, 2020 ; Chou et al., 2021 ; Bastani and Bahrami, 2020 ; Vanderpool et al., 2020 ; Okereke et al., 2020 ; Schiavo, 2020 ; Morgan-Daniel et al., 2020 ; Alvarez-Risco et al., 2020 ; Chong et al., 2020 ; Cichocka, 2020 ; Scerri and Grech, 2020 ; Patel et al., 2020 ; Yu and Mani, 2020 ; Ahmed, 2020 ; Hui et al., 2020 ; Clark-Ginsberg et al., 2020 ; Vraga et al., 2020 ; Sharma et al., 2020 ; Xie et al., 2020 ; Dakhesh et al., 2020 ; Eysenbach, 2002 ; Graham, 2021 ; Morley et al., 2020 ; Vervoort et al., 2020 ; Sperry and Scheibe, 2002 ; Khan et al., 2020 ; Ratzan et al., 2020 ; Hartley and Vu, 2020 ) Empirical studies showed that an empowering intervention was able to significantly reduce the conspiracy beliefs among the public, hence reducing the spreading of rumors ( van Stekelenburg et al., 2021 ; Richardson et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Education and training on health/eHealth literacy were required for the public communities or individuals to increase their ability to differentiate reliable information from the rumors. ( Durodolu and Ibenne, 2020 ; Wormer, 2020 ; Mokhtari and Mirzaei, 2020 ; Mondiale de la Santé, 2020 ; Gottlieb and Dyer, 2020 ; Chou et al., 2021 ; Bastani and Bahrami, 2020 ; Vanderpool et al., 2020 ; Okereke et al., 2020 ; Schiavo, 2020 ; Morgan-Daniel et al., 2020 ; Alvarez-Risco et al., 2020 ; Chong et al., 2020 ; Cichocka, 2020 ; Scerri and Grech, 2020 ; Patel et al., 2020 ; Yu and Mani, 2020 ; Ahmed, 2020 ; Hui et al., 2020 ; Clark-Ginsberg et al., 2020 ; Vraga et al., 2020 ; Sharma et al., 2020 ; Xie et al., 2020 ; Dakhesh et al., 2020 ; Eysenbach, 2002 ; Graham, 2021 ; Morley et al., 2020 ; Vervoort et al., 2020 ; Sperry and Scheibe, 2002 ; Khan et al., 2020 ; Ratzan et al., 2020 ; Hartley and Vu, 2020 ) Empirical studies showed that an empowering intervention was able to significantly reduce the conspiracy beliefs among the public, hence reducing the spreading of rumors ( van Stekelenburg et al., 2021 ; Richardson et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Use of healthcare professionals or scientists as information sources predicts lower susceptibility to health misinformation, as shown in three studies (Richardson et al, 2020;Roozenbeek et al, 2020, study 4;.…”
Section: Behavioral Predictors Of Susceptibility To Health Misinforma...mentioning
confidence: 94%
“…A total of eight studies examined the association between mainstream media use (i.e., general mainstream media use or relying on mainstream media as an information source) and susceptibility to health misinformation. Of the eight studies, four found that mainstream media use is associated with lower susceptibility to health misinformation (Allington et al, 2020, studies 1-2;Richardson et al, 2020;Stecula et al, 2020), two found that mainstream media use increases susceptibility to health misinformation (Melki et al, 2021;van Stekelenburg et al, 2020), and two studies found no relationship (Brian Houston et al, 2021;Jamieson & Albarracín, 2020).…”
Section: Behavioral Predictors Of Susceptibility To Health Misinforma...mentioning
confidence: 99%
“…Thus, many studies have advocated solutions to improve public information literacy, such as education and training programs (Gottlieb and Dyer, 2020; Vraga et al. , 2020; Durodolu and Ibenne, 2020), which have proven to help control misinformation spreading (Richardson et al. , 2020; van Stekelenburg et al.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Summary reviews of information can be applied to handle the vast amount of epidemic information on the internet that places a high health information literacy demand on the users (Dadaczynski et al, 2021;Ros ario et al, 2020;Hsu, 2021). Thus, many studies have advocated solutions to improve public information literacy, such as education and training programs (Gottlieb and Dyer, 2020;Vraga et al, 2020;Durodolu and Ibenne, 2020), which have proven to help control misinformation spreading (Richardson et al, 2020;van Stekelenburg et al, 2021). However, the results of this study revealed that participants demonstrated higher informationseeking abilities and information literacy than before or at the beginning of the epidemic, aligning with other studies such as Zimmerman (2021).…”
Section: Public Information Needs During Covid-19mentioning
confidence: 99%